Complete Thermoelectric Characterization of PEDOT:PSS Thin Films with a Novel ZT Test Chip Platform. Issue 7 (6th February 2018) - Linseis, Vincent; Hassan, Zeinab Mohamed; Reith, Heiko; Garcia, Javier; Nielsch, Kornelius; Baumgart, Helmut; Redel, Engelbert; Woias, Peter
Abstract : For the first time, a complete thermoelectric characterization of PEDOT:PSS thin films is performed with a novel lab‐on‐a‐chip measurement platform, which Is developed for the nearly simultaneous in‐plane ZT characterization. The electrical conductivity, the Seebeck coefficient, the thermal conductivity, and consequently the power factor and ZT values as a function of temperature in a single measurement run is experimentally determined. A clear correlation is found between the film thickness of PEDOT:PSS and the thermoelectric properties. While the electrical conductivity increases with decreasing thickness, the thermal conductivity shows a contrary behavior. Both parameters increase monotonically with increasing temperature between 173 and 373 K. The Seebeck coefficient exhibits the same temperature dependency but, in contrast to the previous two parameters, is almost independent of the PEDOT:PSS film thickness. Furthermore, it is demonstrated that a ZT chip, with a complete set of thermoelectric test structures, can be successfully used for a full thermoelectric characterization of conductive organic thin films. This translates into a major testing time advantage for the screening and optimization of promising organic materials during the R&D phase, which can serve as potential candidates for future thermoelectric applications and devices. Abstract : In this work, a complete thermoelectric characterization of PEDOT:PSS thin films is reported, prepared by spin coating. For the first time, the measurements are performed with a novel lab‐on‐a‐chip measurement platform, which allows the nearly simultaneous characterization of the in‐plane thermal conductivity, electrical conductivity, and Seebeck coefficient of thin films from the micrometer to the nanometer range.